Engineering Xylose Isomerase and Reductase Pathways in Yarrowia lipolytica for Efficient Lipid Production - Isabel De La Torre; Miguel G. Acedos; Juan J. Cestero; Jorge Barriuso; José L. García (Microbial Biotechnology)
ABSTRACT Xylose is a common monosaccharide in lignocellulosic residues that Yarrowia lipolytica cannot naturally metabolise for lipid production and therefore, heterologous xylose metabolic pathways must be engineered in this yeast to facilitate its consumption. We have compared the metabolic efficiency of two xylose metabolic pathways by developing three recombinant Y. lipolytica strains: one harbouring a xylose reductase pathway, one with a xylose isomerase pathway, and one combining both pathways, and the strains were tested for xylose consumption and lipid production at different scales. The recombinant strain with the reductase pathway that was directly isolated in selective xylose medium showed the highest lipid yield, producing up to 12.8 g/L of lipids, or 43% of the biomass dry weight, without requiring any other xylose consumption adaptive evolution process. This strain achieved a lipid yield of 0.13 g lipids/g xylose, one of the highest yields in yeast reported so far using xylose as the sole carbon and energy source. Although the strain harbouring the isomerase pathway performed better under oxygen‐limiting conditions and led to higher lipid intracellular accumulation, it showed a lower xylose uptake and biomass production, rendering a lower yield under non‐limiting oxygen conditions. Unexpectedly, the combination of both pathways in the same strain was less effective than the use of the reductase pathway alone.